Pole-skipping and hydrodynamic analysis in Lifshitz, AdS2 and Rindler geometries - Haiming Yuan; Xian-Hui Ge (Journal of High Energy Physics, 2021)
Abstract The “pole-skipping” phenomenon reflects that the retarded Green’s function is not unique at a pole-skipping point in momentum space (ω, k). We explore the universality of pole-skipping in different geometries. In holography, near horizon analysis of the bulk equation of motion is a more straightforward way to derive a pole-skipping point. We use this method in Lifshitz, AdS2 and Rindler geometries. We also study the complex hydrodynamic analyses and find that the dispersion relations in terms of dimensionless variables ω 2 πT $$ \frac{ω }{2π T} $$ and k 2 πT $$ \frac{\left|k\right|}{2π T} $$ pass through pole-skipping points ω n 2 πT k n 2 πT $$ \left(\frac{ω_n}{2π T},\frac{\left|{k}_n\right|}{2π T}\right) $$ at small ω and k in the Lifshitz background. We verify that the position of the pole-skipping points does not depend on the standard quantization or alternative quantization of the boundary theory in AdS2 × ℝ d−1 geometry. In the Rindler geometry, we cannot find the corresponding Green’s function to calculate pole-skipping points because it is difficult to impose the boundary condition. However, we can still obtain “special points” near the horizon where bulk equations of motion have two incoming solutions. These “special points” correspond to the nonuniqueness of the Green’s function in physical meaning from the perspective of holography.